The Development of the Berliner as a Political Person under the Influence of the Urban Cultural Environment - A. M. Tokarev (Дискурс)
Introduction. The article explores the reasons for the emergence of ethnic diversity in the   city of Berlin, encompassing political, historical, geographical, anthropological, and sociological aspects of the urban environment. It also outlines the current issues in German   society that shape the political culture of its people. The relevance of the topic is driven by   the political radicalization of migrants in Germany, particularly in Berlin, resulting from   cultural globalization that impacts traditional political institutions and behavioral models of   the city's residents. The crisis of the liberal-democratic model and the increase in the   number of Eurosceptics also play a significant role in the transformation of the political   culture of contemporary Berliners. Solving the problem of political radicalization of migrants   is equally important for the Russian Federation, especially in St. Petersburg, combining   characteristics of the European urban environment and the polyethnic Russian state, whose   residents consider themselves Russians despite national and cultural differences.   Methodology and sources. The research is grounded in Ernest Burgess's model of   concentric zones. The study relies on research methods such as synthesis, comparison,   analysis, and sociological approaches. Data from the Federal Statistical Office of Germany,   the results of the 2016 elections to the Berlin House of Deputies, the 2021 elections, and the   subsequent 2023 elections, historical data, and findings from other researchers on the topic   served as sources for the study.  Results and discussion. The study identifies features of urban culture shaping the   polyethnic Berlin society, including the ethnic diversity of residents, unique self-identification   of Berliners, the presence of distinct urban districts, squatter movements, and the influence   of architectural and spatial characteristics on the formation of human social behavior. Some   city problems were also highlighted, such as the crisis of formation of a distorted perception   of right and left currents among Berliners, the failure of multiculturalism policies, the   migration crisis, and housing shortages.   Conclusion. The development of a Berliner as a political being is influenced by the   characteristics of the urban environment and certain issues facing the city, where the   residential district, properties of the city's political culture, and ethnic background impact   the political views of its inhabitants